Socioeconomic adaptation to geomorphological change: An empirical study in Cigu Lagoon, southwestern coast of Taiwan - Phuah, Tony Leong-Keat; Chang, Yang-Chi (Frontiers in Environmental Science, 2023)
Coastal erosion in the lagoon systems is concerned as they are dynamic landscapes, often highly productive and beneficial to humankind. Cigu Lagoon contains rich and diverse ecosystems ranging from mangroves to salt fields, and from fish to birds (e.g., endangered black-faced spoonbill). As well as forming part of the country’s natural defenses against typhoons and storm surges, it is also economically important for oyster farming, fish-pond aquaculture and ecotourism. However, with the construction of reservoir, fishery harbors and breakwaters, sediment transport decreases and sand barrier islands have eroded, narrowed, lowered and moved landwards. Cigu is a rural area with decreasing, aging population, becoming a “super-aged society” as defined by World Health Organization. Therefore, it is imperative to study the socioeconomic impacts of these changes, and then to explore critical adaptation factors and potential adaptation strategies. In this research, we conducted interviews and a fuzzy analytic hierarchy process survey. Diverse stakeholders were identified and mapped using a stakeholder rainbow diagram and a power–interest grid. The results show that stakeholders consider the economy to be the most important adaptation factor, especially in relation to the employment opportunities. There are some forms of livelihood diversification in Cigu. Collaboration among young entrepreneurs is the key to socioeconomic adaptation. These factors and strategies may illuminate socioeconomic adaptation to coastal erosion or geomorphological change, to be aggravated by climate change and other stressors.